Paradigma Pembaharuan Pendidikan Islam Kh. Hasyim As’ari Dalam Upaya Mewujudkan Islam Nusantara - Ehwanudin - Ehwanudin; Sa’dulloh Muzamil (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2018)
This study focuses on one of the figures in the renewal of Islamic education oriented to the wealth and cultural resources of each nation that is nationalism that is KH Hasyim asy'ari. The researcher uses a method of character study to uncover an understanding of the personality of an individual in a particular community and in a particular field, expressing his views, motivations, life history, and ambition as an individual through his or her confession, then analyzed using historical analysis, content analysis. The result of this research is that for academics and the general public, it is necessary to consider the concept of KH Islamic education renewal. Hasyim As'ary that has been done before the age of independence, which today can be felt by the entire nation of Indonesia. In this case KH. Hasyim As'ary introduced the concept of religious education and nationalism that can be used as a pattern of religion and state in diversity like in Indonesia. Keywords: Paradigm, Renewal of Islamic Education, Religion and Nationalism